The Effect of Quality Of Work Life on Employee Loyalty at Pt. X Magelang City - Yunanto, Bagas Prastawa; Wijono, Sutarto (International Journal Labs, 2024)
To advance a company requires maximum contribution from an employee, one of the things that underlies the positive contribution of employees is Loyalty. Loyalty employees is a form of appreciation from employees for the place where they work where they feel a sense of comfort and pride in working. Loyalty can be influenced by many variables, one of that which is quality of work life. Employees with a sense of comfort, experience, satisfaction are things that trigger loyalty in employees. Employees with good quality of work life tend can make better contributions, The purpose of this study is to determine how the quality of work life affects employee loyalty at PT.X Magelang City. This research uses quantitative method with a sample of 40 employees who work at PT.X Magelang City. To measure the quality of work life variable, 8 dimensions of Walton's findings were used, while the loyalty variable used the Employee Loyalty measurement method of Dutta & Dhir. In hypothesis testing, the result obtained is R2 = 17.052 (p<0.05). This finding shows that employees of PT.X Magelang company can work more optimally when they have aspects of loyalty arising from a good sense of quality of work life.